Inhibition of nuclear factor kappaB proteins-platinated DNA interactions correlates with cytotoxic effectiveness of the platinum complexes - Brabec, Viktor; Kasparkova, Jana; Kostrhunova, Hana; Farrell, Nicholas P (Scientific reports, 2016)
Nuclear DNA is the target responsible for anticancer activity of platinum anticancer drugs. Their activity is mediated by altered signals related to programmed cell death and the activation of various signaling pathways. An example is activation of nuclear factor kappaB (NF-κB). Binding of NF-κB proteins to their consensus sequences in DNA (κB sites) is the key biochemical activity responsible for the biological functions of NF-κB. Using gel-mobility-shift assays and surface plasmon resonance spectroscopy we examined the interactions of NF-κB proteins with oligodeoxyribonucleotide duplexes containing κB site damaged by DNA adducts of three platinum complexes. These complexes markedly differed in their toxic effects in tumor cells and comprised highly cytotoxic trinuclear platinum(II) complex BBR3464, less cytotoxic conventional cisplatin and ineffective transplatin. The results indicate that structurally different DNA adducts of these platinum complexes exhibit a different efficiency to affect the affinity of the platinated DNA (κB sites) to NF-κB proteins. Our results support the hypothesis that structural perturbations induced in DNA by platinum(II) complexes correlate with their higher efficiency to inhibit binding of NF-κB proteins to their κB sites and cytotoxicity as well. However, the full generalization of this hypothesis will require to evaluate a larger series of platinum(II) complexes.
Keywords: Protein Binding; Recombinant Proteins; viabilita buněk; adukty DNA; vazebná místa; protinádorové látky; HEK293 buňky; retardační test; Consensus Sequence; Thermodynamics; komplexní sloučeniny; povrchová plasmonová rezonance; platina; Cell Survival; Organoplatinum Compounds; HEK293 Cells; Platinum; Oligodeoxyribonucleotides; Surface Plasmon Resonance; rekombinantní proteiny; termodynamika; oligodeoxyribonukleotidy; vazba proteinů; Binding Sites; kinetika; Coordination Complexes; lidé; konsenzuální sekvence; Humans; DNA Adducts; NF-kappa B; Electrophoretic Mobility Shift Assay; cisplatina; organoplatinové sloučeniny; Cisplatin; Kinetics; Antineoplastic Agents